The Creation of NATO and the Western Alliance - Malia, Alban (European Journal of Multidisciplinary Studies, 2020)
Stalin's actions in eastern Europe evoked fear and uncertainty in the West. The Red Army's fear of a Soviet invasion of the free part of the continent continued to be a major nightmare for post-war Europe. The coup d’etat in Czechoslovakia had the same effect as Stalin's military intervention in Poland. Stalin had ordered to intervene against a country that had great international sympathy for resistance to Hitler in the late 1930s. Whatever Stalin's goal was, he was completely unjustified. The Western Europeans were very afraid. If the Communists did not find it difficult to organize a coup in Prague, what would stop them from doing so in Rome or Paris? And if they tried to do something like that, who would stop them?
Keywords: East, Europe, West, Alliance, Reaction, NATO